Laparoscopic versus open left hemicolectomy for left-sided colon cancer: protocol for a systematic review and meta-analysis - Yang Yang; Yong Wang; Lie Yang; Qiang Du; Jianhao Zhang; Xueting Liu (BMJ Open)
Introduction Laparoscopic colectomy has been widely used clinically due to its minimally invasive advantages, and many studies have also demonstrated its safety and efficacy. However, the efficacy of laparoscopic left hemicolectomy remains unclear due to the differences in pathogenesis and surgical details between left and right colon cancers. Therefore, we plan to conduct a systematic review and meta-analysis to investigate whether laparoscopic techniques can be safely used in left hemicolectomy.Method and analysis This meta-analysis protocol will be completed and reported according to Preferred Reporting Items for Systematic Reviews and Meta-Analyses Protocols guidelines. A systematic search was performed for all articles related to laparoscopic left hemicolectomy in PubMed, Web of Science, Medline, EMBASE and the Cochrane Library from inception to 5 November 2021. Article screening and data extraction were performed independently by two authors and cross-checked after completion. The literature to be included will use corresponding tools for bias risk assessment. Subgroup analyses and sensitivity analyses will be used to explore potential heterogeneity.Ethics and dissemination Because this systematic review is based on studies with published results and does not involve intervention in patients, no ethical review is required. The results of this study will be published in a peer-reviewed journal.PROSPERO registration number CRD42022291526.